Optimize Learning Process during the Covid-19 Pandemic through IT-Based Learning Media at SMPN 10 Bengkulu - Muhammad Fadhli; Sufiyandi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
The Covid-19 pandemic has had a worldwide impact on people's life, notably in the field of education. Online learning is becoming more popular in schools. This situation necessitates the ability of teachers at all levels of education to adapt and innovate in the delivery of online learning. This community service which drew 24 teachers of SMPN 10 Bengkulu City, aimed to strengthen the teachers’ abilities to generate IT-based learning media to improve the school's online learning process through a service-learning approach. As a result of this community service, the teachers have been able to create a learning video using the Kine-master app, develop exercises using Google Forms, and organize virtual classrooms using the Google Classroom program